Kesedihan yang disebabkan oleh Perang dalam “Mieko and the Fifth Treasure” oleh Eleanor Coerr - Muharto Haryono, Tan Theresia; Kurniawan, Yohanes; Kurniawan, Yulius (e-LinguaTera, 2023)
War is a part of human history that is full of grief memories. Literature is a written forum for humanity to remember past events such as war which brought many different reactions and results in life. One of the literary works that portrays the concepts of war, grief, and trauma is “Mieko and the Fifth Treasure” written by Eleanor Coerr. This book was the primary data source of this journal. The purpose of this research was to find the changes due to World War II on the main character “Mieko” and the ways of dealing with her changes, by applying the theory of grief proposed by Kübler-Ross and David Kessler. The main results showed that before the war happened, Mieko was a normal girl who had a wonderful life and loved to make calligraphy art. However, after the war happened, Mieko experienced feelings of fear, confusion, abandonment, insecurity, and many other grief reactions, as a result of her injured hand, her movement to the village, and the bullying she got from some of her classmates. However, Mieko’s friendship with Yoshi slowly turned her negative thoughts into positive ones and made her grow more mature than his past personality. This article wrapped up the essence of healing from visible and invisible wounds that can be done through caring and love for others who are experiencing deep problems in life.